Exploring patient acceptability of a short‐stay care pathway in hospital post arthroplasty: A theory‐informed qualitative study. (30th June 2022) - McDonald, Cassie E.; Paynter, Camille; Francis, Jill J.; Rodda, Daevyd; Bajwa, Supreet; Jackson, Dwane; Story, David
Abstract: Introduction: Arthroplasty is an effective, yet costly, surgical procedure for end‐stage osteoarthritis. Shorter stays in hospital are being piloted in Australia. In some countries, short stay is established practice, associated with improving perioperative care and enhanced recovery after surgery practices. Exploring the acceptability to patients of a short stay care pathway in hospital postarthroplasty is important for informing health policy, adoption and potential scalability of this model of care. Methods: Consecutive patients at one site, at least 3 months post total joint arthroplasty, were invited to participate in theory‐informed semi‐structured qualitative interviews. The Theoretical Framework of Acceptability (TFA) informed development of the interview guide. Interview data were analysed using the Framework Method. Results: Eighteen patients were invited. Fifteen consented to be contacted and were interviewed. Short‐stay post arthroplasty was highly acceptable to patients who had the supports necessary to recover safely at home. Key findings were as follows: flexibility of short‐stay care pathway was essential and valued; prior beliefs and expectations informed acceptability; and the absence of out‐of‐pocket expenses had an incentivizing effect, but was not the primary reason for patients choosing this care pathway. Further themes analysed within the TFA constructs highlighted nuances of acceptability relating to this model of care. Conclusions: A short stay in hospital post arthroplasty appeared to be acceptable to patients who had experienced this care pathway. Our thematic findings identified aspects of the short‐stay care pathway that enhanced acceptability and some aspects that limited acceptability. These findings can inform refinement of the short‐stay care pathway. Patient or Public Contribution: Patients/people with lived experience were not involved in the study design or conduct of this preliminary work; as this short‐stay model of care was recently introduced, only a small group of patients was eligible to participate in this study. This study is the first step towards understanding the experiences of patients about a short‐stay model of care post arthroplasty. The findings will help inform future patient and public involvement in expanding the programme.